Is Geo-Economic Situation Important for the Euro-Atlantic Security System? (Economic and Political Thought, 2013)
The article is an attempt to apply geo-economic analysis to assess thepotential of the U.S. and the EU, and thus for the diagnosis of durabilityand power of the Euro-Atlantic security system. The author believes that thegeo-economic analysis can determine the political and economic potential ofboth main parties to the Euro-Atlantic system, which have a decisive impacton the security and international world order changes.